Sustainability of Freshwater Prawn Culture - New, Michael Bernard; D'Abramo, Louis R.; Valenti, Wagner C. [UNESP]; Singholka, Somsak (Wiley, 2007)
The urgent need to increase the global supply of finfish, molluscs and crustaceans through the expansion of aquaculture activities, in the face of finite supplies from capture fisheries, has been well documented during the 1990s (e.g. New 1991; Hempel 1993; FAO 1997c; New 1997, 1998, 1999b; FAO 1999; Pedini 1999). During that decade the related topics of aquaculture sustainability and responsible aquaculture increasingly became major concerns and were the subject of numerous publications, conferences, and workshops (e.g. Csavas 1993; Reinertsen & Haaland 1995; ADB/NACA 1998; FAO 1998; IFS 1998; Svennevig et al. 1999; Shehadeh 1999). The Food and Agriculture Organization (FAO) Code of Conduct for Responsible Fisheries (FAO 1995) was published and contained a specific section (Article 9) on aquaculture; aquaculture was also included in several other sections of the code (CCRF). The publication of the CCRF was followed by a series of specific technical guidelines for responsible fisheries, including aquaculture (FAO 1997a).The Holmenkollen guidelines for sustainable aquaculture were also drafted (Reinertsen & Haaland 1995) and revised to take account of the CCRF (Svennevig et al. 1999). During this period, the private sector increased efforts to promote aquaculture sustainability itself and to utilise it as a marketing tool. These included the preparation of codes of practice and conduct (e.g. Anonymous 1999a; Boyd 1999; Fegan 1999) and moves towards the promotion of 'organic aquaculture' (Laird 1999a). Discussions about the nature of various aquaculture product certification schemes commenced (e.g. Banks 1998; Anonymous 1999b; Laird 1999b). The need for aquaculture to cultivate its public image in the face of mounting criticism became urgent at this time (New 1999a). This chapter is an examination of the management practices of freshwater prawn farming, which is intended to stimulate discussion about whether it fits within this new aura of responsible and sustainable aquaculture. The major advantages and disadvantages of the culture of Macrobrachium rosenbergii are discussed in a qualitative manner. As yet, there are insufficient data to quantitatively evaluate the social and economic benefits of this form of aquaculture, compared to alternative uses of the resources that it requires (either for aquaculture or other purposes).
Keywords: Environmental benefits of freshwater prawn farming; M. rosenbergii culture; Organic residues; Social benefits of freshwater prawn farming; Sustainability of freshwater prawn culture